Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4161/epi.25798
|View full text |Cite
|
Sign up to set email alerts
|

Methylation loss atH19imprinted gene correlates withmethylenetetrahydrofolate reductasegene promoter hypermethylation in semen samples from infertile males

Abstract: Aberrant methylation at the H19 paternal imprinted gene has been identified in different cohorts of infertile males. The causes of H19 methylation errors are poorly understood. In this study, we investigated the methylation status of the H19 gene in semen DNA samples from infertile males affected by MTHFR gene promoter hypermethylation. DNA from normal and abnormal semen samples harbouring MTHFR gene promoter hypermethylated, hmMTHFR-nor and hmMTHFR-abn, and without MTHFR methylation, MTHFR-nor and MTHFR-abn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 32 publications
0
51
0
Order By: Relevance
“…Methylated region of long QT intronic transcript 1 (DMR-LIT1) is an imprinting control region, and its demethylation is associated with Beckwith-Wiedemann Syndrome [45]. Several studies have demonstrated a significant association between methylation statuses of both maternally and paternally imprinted genes and sperm abnormalities and are summarized in Table 1 [22,38,57,58,[62][63][64][65] (Table 1).…”
Section: Methylation Of Imprinted Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylated region of long QT intronic transcript 1 (DMR-LIT1) is an imprinting control region, and its demethylation is associated with Beckwith-Wiedemann Syndrome [45]. Several studies have demonstrated a significant association between methylation statuses of both maternally and paternally imprinted genes and sperm abnormalities and are summarized in Table 1 [22,38,57,58,[62][63][64][65] (Table 1).…”
Section: Methylation Of Imprinted Genesmentioning
confidence: 99%
“…These epigenetic modifications can be inherited through both mitotic and meiotic divisions. Recent studies demonstrate that aberrant DNA methylation of imprinted genes and reproduction-related genes in particular might be helpful to explain unknown infertility cases [17][18][19][20][21][22]. Therefore, epigenetics appears to be a promising research area for studying idiopathic male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…tensively applied in our life has reproductive toxicity and is shown to disrupt the DNA methylation degree of H19 and Peg3 genes in 8-cell embryos [Zhu et al, 2014]. The regulation of H19 and Peg3 by DNA methylation is correlated with a series of diseases including cancers, diabetes, infertile sperms, as well as poor-thriving embryos [Jiang et al, 2010;Pathak et al, 2010;Ge et al, 2013Ge et al, , 2014Hernanadez-Valero et al, 2013;Rotondo et al, 2013;Lu et al, 2014;Shin et al, 2015]. In this study, we investigated the DNA methylation pattern of H19 and Peg3 during early embryonic development and the effect of sodium fluoride on methylation status.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological changes often ensue from DNA methylation defects. For example, aberrant methylation of the H19 gene is reported to be correlated with infertile sperm, fetal resorption, developmental defects, and poor-quality embryos [Pathak et al, 2010;Hernandez-Valero et al, 2013;Rotondo et al, 2013;Lu et al, 2014;Shin et al, 2015]. A methylation defect of the Peg3 gene is involved in obesity, diabetes, glioma, and reproduction besides its pivotal role in muscle development [Jiang et al, 2010;Ge et al, 2013Ge et al, , 2014.…”
mentioning
confidence: 99%
“…It is vital for providing sufficient methyl groups for DNA synthesis and methylation and is thought to have an important role in spermatogenesis due to its association with low sperm count and non-obstructive azoospermia [66,67]. MTHFR promoter hypermethylation has been strongly associated with idiopathic male infertility [62], and interestingly, this hypermethylation seems to occur alongside hypomethylation of H19 [69]. Given the role of MTHFR in normal methylation, this could have consequences for other genes.…”
Section: Dna Methylation In Sperm Function and Male Infertilitymentioning
confidence: 99%